2015
DOI: 10.1016/j.matpr.2015.05.069
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Nanostructured Tetrathiotetracene Iodide Crystals: 3D Modeling

Abstract: A more complete three-dimensional (3D) physical model for nanostructured crystals of tetrathiotetracene iodide, TTT 2 I 3 , is presented. The restrictions on the thermoelectric figure of merit ZT that this model involves are determined. At the same time, the criteria of application of simplified 1D model are defined more precisely. In TTT 2 I 3 crystals the carriers are holes. As earlier, two interaction mechanisms of holes with acoustic phonons are considered, generalized for 3D case. One interaction is simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…41 Organic materials whose thermoelectric properties have been studied 42 include polymers such as poly(thienothiophene), 43 poly(ethylene-dioxythiophene) [44][45][46][47][48][49][50] (PEDOT), polyaniline, 51 poly(pphenylene vinylene) derivatives, 52,53 poly(3-hexylthiophene), 1,54 carbazole polymers, [55][56][57] metal coordination polymers, 58 and P(NDIOD-T2) 59 , as well as small molecules such as fullerenes, [60][61][62][63] perylene diimide derivatives and organic salts based on TTF, TCNQ, BEDT-TTF and tetrathiotetracene amongst others. 44,[64][65][66][67][68][69][70] Of these, PEDOT has recently shown excellent performance as a p-type thermoelectric material with ZT reported up to 0.42 71 . On the other hand, there has not been so much success in finding good n-type organic thermoelectric materials.…”
Section: = ⁄ (4)mentioning
confidence: 99%
“…41 Organic materials whose thermoelectric properties have been studied 42 include polymers such as poly(thienothiophene), 43 poly(ethylene-dioxythiophene) [44][45][46][47][48][49][50] (PEDOT), polyaniline, 51 poly(pphenylene vinylene) derivatives, 52,53 poly(3-hexylthiophene), 1,54 carbazole polymers, [55][56][57] metal coordination polymers, 58 and P(NDIOD-T2) 59 , as well as small molecules such as fullerenes, [60][61][62][63] perylene diimide derivatives and organic salts based on TTF, TCNQ, BEDT-TTF and tetrathiotetracene amongst others. 44,[64][65][66][67][68][69][70] Of these, PEDOT has recently shown excellent performance as a p-type thermoelectric material with ZT reported up to 0.42 71 . On the other hand, there has not been so much success in finding good n-type organic thermoelectric materials.…”
Section: = ⁄ (4)mentioning
confidence: 99%
“…Recently, it was shown that Advances in Materials Physics and Chemistry highly conducting Quasi-One-Dimensional (Q1D) organic crystals can have different promising thermoelectric applications [4] [5]. It was predicted in [6] that the values of dimensionless thermoelectric figure of merit ~4 could be realized after optimization of carrier concentration in TTT 2 I 3 organic crystals. On the other hand, it is well known that organic nanomaterials have large potential applications in electronic, sensing, energy-harnessing and quantum-scale systems [7].…”
Section: Introductionmentioning
confidence: 99%